2016
DOI: 10.1002/pmic.201500129
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana root cell wall proteomics: Increasing the proteome coverage using a combinatorial peptide ligand library and description of unexpected Hyp in peroxidase amino acid sequences

Abstract: Plant cell walls (CWs) contain a large proportion of polysaccharides (90-95% of CW mass) and proteins (5-10%) that play major roles in CW plasticity during development and in response to environmental cues. Here, we present CW proteomics data of Arabidopsis thaliana roots. Plants were cultivated in hydroponic conditions. CW protein (CWP) extracts were prepared and analyzed in two different ways in order to enlarge the coverage of the root CW proteome: proteins were analyzed either directly or following an affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 94 publications
5
33
0
1
Order By: Relevance
“…While some of the apoplastic proteins are normally classified as intracellular proteins, such as Varicose (AT3G13300) or NADP-malic enzyme 2 (AT5G11670), they have recently been found in extracellular/cell wall or plasma membrane proteomes (De Michele et al, 2016; Nguyen-Kim et al, 2016). In particular, these also include six members of the Histone 2A family (Table 1), which are typically part of the core nucleosomes (Mitra et al, 2009; Heard et al, 2015; Nguyen-Kim et al, 2016). However, other histones such as Histone 4 have previously also been reported in pea root cap secretome (Wen et al, 2007), suggesting possible extracellular functions of histones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While some of the apoplastic proteins are normally classified as intracellular proteins, such as Varicose (AT3G13300) or NADP-malic enzyme 2 (AT5G11670), they have recently been found in extracellular/cell wall or plasma membrane proteomes (De Michele et al, 2016; Nguyen-Kim et al, 2016). In particular, these also include six members of the Histone 2A family (Table 1), which are typically part of the core nucleosomes (Mitra et al, 2009; Heard et al, 2015; Nguyen-Kim et al, 2016). However, other histones such as Histone 4 have previously also been reported in pea root cap secretome (Wen et al, 2007), suggesting possible extracellular functions of histones.…”
Section: Resultsmentioning
confidence: 99%
“…a The PubMed ID (PMID) of the publication reporting the plasma membrane (PM), extracellular or plastid proteomics data are indicated: Nguyen-Kim et al, 2016 (PMID:26572690); Mitra et al, 2009 (PMID:19334764); Heard et al, 2015 (PMID:25900983); De Michele et al, 2016 (PMID:26781341); Charmont et al, 2005 (PMID:15694452); Zhang and Peck, 2011 (PMID:21433285); Helm et al, 2014 (PMID:24361574); Melonek et al, 2016 (PMID:26987276) .…”
Section: Resultsmentioning
confidence: 99%
“…It represented almost a quarter of the total number of CWPs, a proportion which has been found in the cell wall proteomes of various organs of B. distachyon , A. thaliana and O. sativa [15,32,33,34,35]. GHs, expansins, CEs and PNGases were the most represented protein families in the cell wall proteomes of the B. distachyon grain.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of the rosette cell wall proteome to those of other A. thaliana organs has shown that 219 CWPs were common with that of roots [21][22][23], 64 to that of stems [24] and 135 to that of etiolated hypocotyls [11,12,25]. Besides, 109 CWPs were common to the cell wall proteomes of rosettes and cell suspension cultures [26][27][28][29][30][31] (Table 1).…”
Section: Abstract: Arabidopsis Thaliana / Cell Wall / Leaf / Plant Prmentioning
confidence: 99%